transformational leadership in developing case studies in the ulil abshor foundation - sigit wahyu utomo (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
The purpose of this study is to prove that transformational leadership styles can be applied to the development of the ulil abshar foundation, the poor qualitative descriptive research USES adhesive techniques. Data collection techniques using interviews, observations and documentation the many phenomena that researchers have found in some vayasan vakni many vang children enter yavasan but do not receive a lava education, where children often break the rules. With this application of transformational leadership style, it provides some positive impact. The role of head of a foundation can help create an example for subordinates and foster children. Then with this research. The writer hopes that this transformational leadership style can be applied in social institutions that have not been mastering using this leadership style